2015
DOI: 10.7196/samj.2016.v106i1.10149
|View full text |Cite
|
Sign up to set email alerts
|

Taking kangaroo mother care forward in South Africa: The role of district clinical specialist teams

Abstract: The global agenda for improved neonatal care includes the scale-up of kangaroo mother care (KMC) services. The establishment of district clinical specialist teams (DCSTs) in South Africa (SA) provides an excellent opportunity to enhance neonatal care at district level and ensure translation of policies, including the requirement for KMC implementation, into everyday clinical practice. Tshwane District in Gauteng Province, SA, has been experiencing an increasing strain on obstetric and neonatal services at cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…6 Center of Bioethics for Eastern & Southern Africa (CEBESA), Blantyre, Malawi. 7 Department of Pathology and Laboratory Medicine, BC Children's and Women's Hospital, University of British Columbia, Vancouver, Canada.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Center of Bioethics for Eastern & Southern Africa (CEBESA), Blantyre, Malawi. 7 Department of Pathology and Laboratory Medicine, BC Children's and Women's Hospital, University of British Columbia, Vancouver, Canada.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Effective KMC practice involves a multidisciplinary team [7] that centers on the newborn's caregiver to deliver the care with support from health workers [4]. In addition to skin-to-skin contact and supporting exclusive breastfeeding, a key component of KMC is the goal of early discharge from the hospital [8], which requires caregiver knowledge and acceptance [6].…”
Section: Introductionmentioning
confidence: 99%
“…It strengthens capacity for and value of monitoring. Other studies on implementing KMC in sub-Saharan Africa identified maternal emotional and practical support from health workers as a key enabler for the practice [18,19,21,[30][31][32][33][34].…”
Section: Investment In Staffingmentioning
confidence: 99%
“…19 20 Skill-based KMC training and reorientation improves the quality of care. [21][22][23][24] In a quality improvement project, Joshi et al improved KMC with simple measures involving family members, positive reinforcement and felicitation of healthcare workers. 25 26 In the initial phase, we aimed to improve the coverage of KMC in admitted eligible neonates from a baseline of 20%-80% within 15 days.…”
Section: Key Messagesmentioning
confidence: 99%